2013
DOI: 10.1371/journal.pone.0073324
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in the Strength of Plant-Herbivore Interactions under Predation Risk: The Tale of Bison Foraging in Wolf Country

Abstract: Spatial heterogeneity in the strength of trophic interactions is a fundamental property of food web spatial dynamics. The feeding effort of herbivores should reflect adaptive decisions that only become rewarding when foraging gains exceed 1) the metabolic costs, 2) the missed opportunity costs of not foraging elsewhere, and 3) the foraging costs of anti-predator behaviour. Two aspects of these costs remain largely unexplored: the link between the strength of plant-herbivore interactions and the spatial scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…As such, the anti‐predator movement tactics of large herbivores are not restricted to the shell games typically observed in the predator–prey spatial games of large species (e.g. Laundré ; Harvey & Fortin ; Courbin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the anti‐predator movement tactics of large herbivores are not restricted to the shell games typically observed in the predator–prey spatial games of large species (e.g. Laundré ; Harvey & Fortin ; Courbin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the preferential use of forest gaps by deer in BPF (Kuijper et al 2009), they cannot support long-term occupation by ungulates due to their small size. This contrast to heterogeneous landscapes with both forest and large open spaces, where prey aggregates for considerable amount of time in open habitat (Courant and Fortin 2012;Harvey and Fortin 2013). In our study area, deer use the forest gaps only for short periods of time, with each patch visited less than 2 min, meaning that most of the time they are present in closed forest habitat (Kuijper et al 2009).…”
Section: Effects Of the Landscape Structurementioning
confidence: 91%
“…Other potential prey for wolves in PANP included elk Cervus canadensis , white‐tailed deer Odocoileus virginianus , mule deer Odocoileus hemionus , moose Alces alces and beaver Castor canadensis . While direct predation on adult bison appears to be generally infrequent in PANP (Harvey and Fortin ), investigation of wolf kill sites identified by clusters of GPS locations (Webb et al ) revealed a minimum of 8 adult bison killed by wolves during the late winter of –2014. Moreover, several bison in PANP show signs of altercation with wolves (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several bison in PANP show signs of altercation with wolves (e.g. missing tails, Harvey and Fortin ). Wolves are also reported to preferentially prey upon bison calves (Carbyn and Trottier , Metz et al ), )a pattern which should trigger attacks on bison groups from spring to autumn (Carbyn and Trottier ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation